A microcalorimetric and microscopic strategy to assess the interaction between dietary fibers and small molecules. (1st July 2022) - Lupo, Cristina; Boulos, Samy; Gramm, Fabian; Wu, Xiaowen; Nyström, Laura
Abstract: The interaction between small molecules and neutral soluble dietary fiber is one of the proposed mechanisms determining the bioavailability of these components in the small intestine. However, the weak nature of these interactions makes it difficult to find an analytical method sensitive enough to detect them. Here, we probed the molecular interaction between galactomannan, arabinoxylan, and β-glucan with gallic acid, cinnamic acid, acetylsalicylic acid, and acetaminophen, using advanced analytical methods, namely isothermal titration calorimetry (ITC) and in the form of gold-nanoparticles, transmission electron microscopy (TEM). The results obtained from ITC analysis were fully consistent with the results obtained from TEM. In short, the interaction of these fibers and small molecules was mainly entropically driven, hence involving hydrophobic type association and possible conformational changes of the polysaccharide. However, the enthalpy contribution (hydrogen interaction) is also significant, especially regarding interactions with the acetylsalicylic acid molecule. Graphical abstract: Unlabelled Image